Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, Malang - Syafa'ah, Asna Ullya Rahma (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of Inclusive Education Policy Based on Student With Disabilities Perception Study in Brawijaya University, Malang. Inclusive Education Policy that has been implemented in Brawijaya University since 2012 has meet some difficulties in the process of the implementation. The difficulties are generally experienced by student with disabilities as an object of the policy itself, for example, there are a lot of misunderstanding about the policy so it caused a lot of the facilities are not well functioned. Some actors as policy makers also not being able to fulfill disability awareness toward student with disabilities completely. The result from this research shows that implementation of inclusive education has been well implemented with some research focuses on standard of inclusive education policy, the institution as an administrator in inclusive education policy, the facilities used in inclusive education policy, and internal environment of inclusive education. The recommendations from this research, especially for Brawijaya University and Pusat Studi dan Layanan Disabilitas Universitas Brawijaya (PSLD UB) are to conduct a reselection for the student with disabilities that has been accepted in Brawijaya University other than Seleksi Program Khusus Penyadang Disabilitas (SPKPD). Also, it needs monitoring for the facilities used in inclusive education policy in Brawijaya University as a supporting to inclusive education. Keyword:Policy Implementation, Inclusive Education Abstrak: Implementasi Kebijakan Pendidikan Inklusif Berdasarkan Persepsi Mahasiswa Penyandang Disabilitas Studi di Universitas Brawijaya, Malang. Kebijakan pendidikan inklusif yang telah diterapkan di Universitas Brawijaya sejak tahun 2012 mengalami beberapa kendala dalam penerapannya. Kendala ini pada umumnya dialami oleh penyandang disabilitas sebagai penerima kebijakan, misalnya banyak ketidak pahaman mengenai kebijakan itu sendiri hingga banyaknya penyalahgunaan fasilitas. Beberapa aktor yang menjadi pemegang kebijakan juga dirasa penyadang disabilitas belum memenuhi disabity awareness dengan cukup baik. Hasil dari penelitian ini menunjukan bahwa Implementasi pendidikan inklusif sudah berjalan baik dengan beberapa fokus penelitian pada standart kebijakan pendidikan inklusif, lembaga pengelola kebijakan pendidikan inklusif, sarana dan prasarana, serta lingkungan internal pendidikan inklusif. Rekomendasi dari penelitian ini khususnya untuk Universitas Brawijaya dan Pusat Studi dan Layanan Disabilitas Universitas Brawijaya (PSLD UB), melakukan penyeleksian ulang mahasiswa penyandang disabilitas yang masuk melalui jalur selain Seleksi Program Khusus Penyandang Disabilitas (SPKPD). Perlu adanya pengawasan terkait dengan adanya sarana dan prasarana yang telah ada di Universitas Brawijaya sebagai penunjang pendidikan Inklusif. Â  Kata kunci : Implementasi Kebijakan, Pendidikan Inklusif